Journal of Venomous Animals and Toxins including Tropical Diseases - Barraviera, Benedito; Martins, Selma; Simionato, Juliana
Journal of Venomous Animals and Toxins including Tropical Diseases (JVATiTD) is an open access interdisciplinary publication, dedicated to research on all aspects of toxins, venomous animals and their derivative products. The journal also welcomes submissions related to tropical diseases with a focus on infectious diseases, parasitology and immunology. The journal accepts submissions on toxins derived from animals, plants and microorganisms. Topics of interest include, but are not limited to: systematics and morphology of venomous animals physiology, biochemistry, pharmacology and immunology of toxins epidemiology, clinical aspects and treatment of envenoming by different animals, plants and microorganisms development and evaluation of antivenoms and toxin-derivative products epidemiology, clinical aspects and treatment of tropical diseases (caused by virus, bacteria, algae, fungi and parasites) including the neglected diseases defined by the World Health Organization.